2021
DOI: 10.3389/fpsyg.2021.666027
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Malaysian Media Intervention Workshop: Safe Reporting on Suicide

Abstract: Background: Suicide remains an important cause of premature deaths and draws much media attention. However, unsafe reporting and portrayal of suicides by the media have been associated with increased risk of suicidal behavior. Current evidence suggests that media capacity-building could potentially prevent suicide. However, there are still knowledge gaps in terms of a lack of data on effective strategies for improving awareness and safe reporting of suicide-related media content. This study aims to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This intervention study involved a sample of healthcare workers and lecturers in UKM to evaluate the effectiveness of an online gatekeeper suicide prevention training program among healthcare lecturers. Analysis of each individual item ( 53 ) in AdCARE-Q has helped us to have a better understanding of the outcome of this program which will allow us to have a targeted approach to improve suicide literacy in the future. The study outcome has shown that Online AdCARE effectively improves participants’ overall improvement in preventing suicide, especially in the Self-Efficacy (SE) domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intervention study involved a sample of healthcare workers and lecturers in UKM to evaluate the effectiveness of an online gatekeeper suicide prevention training program among healthcare lecturers. Analysis of each individual item ( 53 ) in AdCARE-Q has helped us to have a better understanding of the outcome of this program which will allow us to have a targeted approach to improve suicide literacy in the future. The study outcome has shown that Online AdCARE effectively improves participants’ overall improvement in preventing suicide, especially in the Self-Efficacy (SE) domain.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the program, Online AdCARE adhered to the principle of safe messaging while facilitators intermittently checked on participants’ current emotional states for discussing suicide may be distressing to some individuals. The program also applied the standard of moderation in responsible suicide reporting by Duncan and Luce ( 53 , 74 ). It suggests the practice of safe information by not including sensitive graphical details while practicing the proper use of tone and language when discussing suicide.…”
Section: Discussionmentioning
confidence: 99%